Peran Produk, Harga dan Promosi dalam Meningkatkan Daya Saing - Andestiawan, Andestiawan; Novi Peramasari; Mustika Mustika (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This research aims to analyze the role of marketing strategies, specifically product, price, and promotion variables, in enhancing company competitiveness amidst dynamic market competition. This study uses a qualitative approach with literature review and meta-analysis methods, examining various scientific journals, books, and relevant secondary references. The result indicate that product through high quality, innovation, and differentiation, price through competitive pricing balanced with value, and promotion through effective marketing communication and brand awareness creation significantly play a direct role in increasing competitiveness. Beyond these three main elements, competitiveness is also influenced by other supporting factors such as social media usage, viral marketing, atmosphere, and strategic location. Thus, implementing integrated marketing management focused on optimizing product, price, and promotion serves as a key strategy for companies to build sustainable competitive advantage.